PENGARUH BUDAYA ORGANISASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT SAMMYUNG PRECISION BATAM - Efi lorinka; Winda Evyanto (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
In the current era of globalization, technological developments are closely related to Human Resources. This development certainly requires resources that have a high level of creativity and potential, especially for companies. This study aims to review the extent to which the role of organizational culture and work discipline on employee performance. PT Sammyung Precision Batam is a company that was founded in 2019 and is engaged in manufacturing. The researcher conducted a study using non-probability sampling, with a sample size of 113 people. and the method used is quantitative method and the data analysis method used is descriptive analysis which includes: data quality test, validity test, reliability test, classical assumption test, normality test, multicollinearity test and heteroscedasticity test. In this study, the data was processed using SPSS Version 25 with the results of the study known that the T count was 1.6588 > 2.990 and the significant value was 0.006 < 0.05, which means that organizational culture has a positive and significant effect on employee performance. discipline is known to have T count of 2.777 > 1.6588 and its significant value is 0.009 < 0.05, meaning that discipline has a positive and significant effect on employee performance. then there is a positive and significant influence simultaneously (together) between organizational culture, discipline on employee performance at PT Sammyung Precision Batam can be seen from the F value of 32.854 (F count) > 2.6871 (F table) with a significant value of 0.000 < 0.05